下顎骨関節突起骨折に対するTransmasseteric Anteroparotid(TMAP)アプローチを用いた観血的整復術の経験 - 宮本, 日出雄; 野里女, 明代; 濱田, 啓一; 原園, 陽介; 長谷川, 和樹 (日本口腔外科学会雑誌, 2018)
Fractures of the mandibular condyle are common and account for 25% to 50% of all mandibular fractures. Even with the development of a consensus on the preference for open reduction and internal fixation (ORIF) of these fractures, the optimal approach to the fracture unit remains controversial. Nine patients with mandibular condylar fractures underwent ORIF using a transmasseteric anteroparotid (TMAP) approach between 2010 and 2016. Here, we describe the approach, including its surgical technique and results. The study group comprised three men and six women who were 26 to 80 years of age. A TMAP approach was indicated for subcondylar or condylar neck fractures. In most cases, successful ORIF was achieved. However, one patient had plate loss. No patient had facial nerve palsy or salivary fistula. This approach adequately exposes the fracture end, enabling completion of ORIF under direct visualization, although it does not present with a large operative field. Moreover, we can extend the skin incision depending on various fracture sites, allowing multiple directional approaches to the fracture site. A TMAP approach is considered to be one of choices for ORIF of mandibular condylar fractures and the indications of this approach should be examined more carefully.